THE PLACES OF SETTLEMENT OF THE KOREANS IN THE PRIMORSKY REGION AS A FACTOR OF ENHANCING CULTURAL TOURISM IN THE REGION - VLASENKO, Albina Alekseevna; TSAREVA, Natalia Aleksandrovna (Journal of Environmental Management and Tourism, 2016)
The article considers one of the possible variants of using tourist potential of the southern Far East. The places of resettlement of Korean immigrants of the 19th century on the territory of Primorsky Region and the specifics of their life have been identified. It is proposed to use the places of settlement of the Koreans to enhance inbound tourism in the Primorsky Region, by immersion of immigrants from Korea in a re-created socio-cultural environment in all forms of its manifestation. The concept of creating a competitive tourism product, demanded by tourists from the Republic of Korea, China and Japan, in the future is proposed. A Korean ethno village may be included in tourist routes, where tourists can get acquainted with the history of resettlement of the Koreans to Russia, Korean culture and traditions. The Korean ethno village, created as a multifunctional complex with the purpose of organization of leisure time of the population and inbound tourists, as well as the guests’ acquaintance with the Korean culture, traditions and rituals, will help to balance the tourist market of the Primorsky Region. The implementation of the concept of the Korean ethno village creation will entail improving the welfare and comfort of living of population of the southern Primorsky Region due to the development of infrastructure for recreation and tourism.
Keywords: cultural tourism; Korean immigrants; Primorsky region; ethno village